A composite foam material and its preparation method and application

The compatibility and bond strength of the plant fibers with the thermoplastic material matrix are improved by treating the plant fibers with the use of lye and combining coupling agents and nano-inorganic particles. Combined with the supercritical gas microporous foaming process, composite foaming materials with excellent mechanical properties and low density were prepared, solving the problems of delamination, poor bonding interface, and degradation of toughness in the existing materials during the molding process.

CN118374091BActive Publication Date: 2025-04-22GAC HONDA AUTOMOBILE CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410589047.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-13
Publication Date
2025-04-22
Estimated Expiration
2044-05-13

AI Technical Summary

Technical Problem

The existing plant fiber reinforced composite materials have problems such as delamination, poor bonding interface, decreased toughness, non-reduced density and unstable cell during the molding process, which limits its large-scale industrial application.

Method used

Plant fibers are treated with alkali liquid to improve their compatibility with the thermoplastic material matrix, and the binding strength is enhanced by the addition of coupling agent and nano-inorganic particles. Combined with the supercritical gas microporous foaming process, composite foaming materials with excellent mechanical properties and low density were prepared.

Benefits of technology

It significantly improves the mechanical properties of composite foaming materials, including bending strength, tensile strength and impact strength, while reducing the density of the material, solving the problems of cell instability and material brittleness, and is suitable for applications such as automotive parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004836670590000091
    Figure BDA0004836670590000091
  • Figure BDA0004836670590000092
    Figure BDA0004836670590000092
  • Figure HDA0004836670600000011
    Figure HDA0004836670600000011
Patent Text Reader

Abstract

The present invention discloses a composite foam material and a preparation method and application thereof. The composite foam material comprises the following raw materials in parts by weight: 45-85 parts of thermoplastic material, 10-40 parts of fiber material, 3-9 parts of coupling agent, 3-9 parts of nano inorganic particles, and 8-12 parts of toughening agent; the fiber material is alkali-treated plant fiber. The composite foam material of the present invention has good interface compatibility between the fiber material and the thermoplastic material matrix, has good interface micromorphology, improves the compatibility between the fiber material and the thermoplastic material matrix, improves the mechanical properties of the composite foam material, and has the lightweight characteristics of low density and light weight.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of materials, and in particular relates to a composite foaming material and a preparation method and application thereof. Background Art

[0002] Plant fibers come from natural plants, such as cotton, hemp, straw, rice husks, wood and bamboo. They have the advantages of light weight, wide sources, low cost, easy to obtain, renewable and degradable. They are a green and environmentally friendly biomass resource. The injection molding process has many advantages and is suitable for large-scale production of industrial parts. It is an important molding method for plant fiber reinforced composite materials. In the current industrial world, environmental protection and lightweight are important development directions of parts technology in the fields of aircraft, automobiles, etc. For the supercritical gas microporous foaming injection molding process, the presence of plant fibers promotes the nucleation of bubbles, and can effectively prepare products with micropores inside, which reduces the quality of the products and meets the lightweight needs of the industry. However, the existing parts made of plant fiber reinforced composite materials by injection molding generally have the following problems, which greatly limits their large-scale industrial application:

[0003] (1) The abundant hydroxyl groups on the surface of plant fibers have high water absorption, which leads to delamination between plant fibers and polymer matrix. At the same time, plant fibers are polar materials, and polymer matrix is ​​often non-polar materials. The two are incompatible during the molding process, resulting in a poor bonding interface and weakening the mechanical properties of plant fiber reinforced composites.

[0004] (2) As the plant fibers are dispersed in the polymer matrix, micropores are inevitably generated at the junction between the plant fibers and the polymer matrix. If limited filling is not performed, the mechanical properties of the composite material will be further damaged.

[0005] (3) The addition of plant fibers causes the composite material to become harder and more brittle compared to the polymer matrix, resulting in a decrease in the toughness of the composite material.

[0006] (4) The lightweight advantages of traditional plant fiber reinforced composite injection molded parts over pure polymer matrix are not obvious;

[0007] (5) Chemical foaming increases the microporous structure and reduces the density, which poses a risk of unstable cells. At the same time, foam products made with foaming agents have a short service life and are prone to aging and damage. Summary of the invention

[0008] In order to overcome at least one technical problem existing in the above-mentioned prior art, one of the objectives of the present invention is to provide a composite foam material.

[0009] A second object of the present invention is to provide a method for preparing a composite foam material.

[0010] A third object of the present invention is to provide an automobile component.

[0011] A fourth object of the present invention is to provide an application of a composite foam material in an automobile.

[0012] In order to achieve the above object, the technical solution adopted by the present invention is:

[0013] The first aspect of the present invention provides a composite foaming material, comprising the following raw materials in parts by weight: 45 to 85 parts of thermoplastic material, 10 to 40 parts of fiber material, 3 to 9 parts of coupling agent, 3 to 9 parts of nano inorganic particles, and 8 to 12 parts of toughening agent; the fiber material is alkali-treated plant fiber.

[0014] The present invention adopts alkali solution to treat plant fibers, so that impurities such as hemicellulose, gum, wax, etc. in the plant fibers can be dissolved in the alkali solution, thereby purifying the plant fibers. In addition, the alkali solution is used to treat the plant fibers, so that the surface of the plant fibers is loose and porous, and the surface roughness is increased, thereby improving the compatibility between the fiber material and the thermoplastic material matrix, improving the contact interface between the two, and cross-linking through a coupling agent is beneficial to improving the bonding strength between the fiber material and the thermoplastic material matrix, solving the problems of short service life, material brittleness, easy damage, etc. caused by delamination during use of existing plant fiber composite materials and mechanical weak points inside the materials, thereby improving the mechanical strength of the composite foam material in the present invention.

[0015] Preferably, the composite foam material is a supercritical gas foaming molding material. The present invention adopts supercritical gas foaming. After foaming, the pore size of the composite foam material is uniform, and no additives such as foaming agents are needed, which effectively solves the problems of uneven foaming and aging durability. The equipment process is simple, the cost is low, and it is green and environmentally friendly.

[0016] Preferably, the supercritical gas is selected from nitrogen, carbon dioxide or a combination thereof.

[0017] Preferably, the thermoplastic material is selected from at least one of polypropylene, polystyrene, polyethylene, polyvinyl chloride, polycarbonate, polyamide, and polyacrylate.

[0018] Preferably, the polypropylene has a melt index of 10 to 30 g / 10 min measured at 230° C. and a load of 2.16 kg.

[0019] Preferably, the plant fiber is selected from at least one of bamboo fiber, wood fiber, paper fiber, hemp fiber and straw fiber.

[0020] Preferably, the coupling agent is selected from polypropylene grafted with acrylic acid; further preferably, the coupling agent is selected from polypropylene grafted with maleic anhydride.

[0021] Preferably, the nano inorganic particles are selected from nano montmorillonite. The role of the nano inorganic particles in the present invention is to fill the micropores inside the plant fiber and between the plant fiber and the thermoplastic material, avoid mechanical weaknesses inside the composite foam material, and thus improve the overall strength and toughness of the material.

[0022] Preferably, the toughening agent is selected from SEBS. SEBS is a linear triblock copolymer with polystyrene as the terminal segment and ethylene-butene copolymer obtained by hydrogenating polybutadiene as the middle elastic block. The synergistic effect between SEBS and nano inorganic particles can improve the tensile strength and toughness of the composite foam material.

[0023] Preferably, the preparation method of the fiber material is: soaking the plant fiber in alkali solution at 50-70°C for 1-10 hours, and then washing, drying and crushing it to obtain the fiber material; further preferably, the preparation method of the fiber material is: soaking the plant fiber in alkali solution at 55-65°C for 3-6 hours, and then washing, drying and crushing it to obtain the fiber material.

[0024] Preferably, the washing step comprises: washing the plant fibers with distilled water until the pH of the washed water is neutral.

[0025] Preferably, the alkali solution is selected from sodium hydroxide solution, potassium hydroxide solution or a combination of the two.

[0026] Preferably, the flexural strength of the composite foam material is not less than 55 MPa; further preferably, the flexural strength of the composite foam material is 55-60 MPa.

[0027] Preferably, the tensile strength of the composite foam material is not less than 30 MPa; further preferably, the tensile strength of the composite foam material is 31-33 MPa.

[0028] Preferably, the impact strength of the composite foam material is not less than 6KJ / m 2 ; Further preferably, the impact strength of the composite foam material is 6.5 to 7.0 KJ / m 2 .

[0029] Preferably, the average pore diameter of the composite foam material is 15 to 30 μm.

[0030] Preferably, the cell density of the composite foam material is 2×10 6 ~1.6×10 7 Pieces / cm 3 .

[0031] Preferably, the density of the composite foam material is 0.75-0.9 g / cm 3 .

[0032] Preferably, the porosity of the composite foam material is 10-20%.

[0033] The composite foam material in the present invention is prepared by introducing supercritical gas (for example: N2) into the injection molding process after the raw materials are premixed for integrated foaming molding. The composite foam material has the appearance of plant fiber color, and through the surface treatment of the plant fiber and the addition of a coupling agent, the plant fiber and the polymer matrix produce excellent interface compatibility, and through the synergistic effect of nano inorganic particles and high-efficiency toughening agents, the tensile strength and toughness of the composite foam material are greatly improved, and through the supercritical gas microporous foaming molding process, the density of the composite foam material is effectively reduced. The micropores inside the lightweight composite foam material have the function of resisting the generation of micro cracks and absorbing energy, so it has good impact resistance, high mechanical properties, and good heat insulation and sound absorption performance. The products containing the composite foam material have the advantages of low density, light weight, and low cost, meet the lightweight requirements, and can be applied to automotive parts, such as: micro-foamed automotive interior and exterior decoration parts, instrument panels, compartment floors, seat backs and armrests, etc., and have good application prospects and industrial value.

[0034] The second aspect of the present invention provides a method for preparing the composite foam material provided by the first aspect of the present invention, comprising the following steps:

[0035] S1: mixing the prepared raw materials and then extruding and granulating them to obtain masterbatch;

[0036] S2: injection molding the masterbatch, and using supercritical gas foaming during the injection molding process to obtain the composite foam material.

[0037] Preferably, the step S1 is: mixing the raw materials, extruding and granulating, and then drying at 100-150° C. for 4-10 hours to obtain master batches.

[0038] Preferably, the extrusion granulation step is: melt extrusion granulation is performed using an extruder, and the temperature of the extruder is set to: zone 1 temperature is 170-175°C, zone 2 temperature is 175-185°C, zone 3 temperature is 185-195°C, zone 4 temperature is 185-195°C, and zone 5 temperature is 175-185°C.

[0039] Preferably, the injection molding step comprises: injection molding the masterbatch using an injection molding machine; the temperature of the injection molding machine is set as follows: the temperature of zone 1 is 180-185°C, the temperature of zone 2 is 185-195°C, the temperature of zone 3 is 185-195°C, and the temperature of zone 4 is 180-185°C.

[0040] Preferably, in the injection molding step, the mold temperature is 40-50°C.

[0041] Preferably, the step S2 is to injection mold the masterbatch, use supercritical gas for foaming during the injection molding process, and then cool to obtain the composite foam material.

[0042] Preferably, in the cooling step, the temperature of the cooling liquid is 20-30°C.

[0043] Preferably, the cooling time is 15 to 25 seconds.

[0044] Preferably, the mass ratio of the supercritical gas to the raw material for preparing the composite foaming material is (0.5-1):100.

[0045] Preferably, the pressure of the supercritical gas is 15-22 MPa.

[0046] The third aspect of the present invention provides an automobile component, comprising the composite foam material provided by the first aspect of the present invention.

[0047] Preferably, the automobile parts include automobile interior decoration parts, automobile exterior decoration parts, instrument panels, automobile compartment floors, automobile seat backs, and automobile armrests.

[0048] The fourth aspect of the present invention provides use of the composite foam material provided by the first aspect of the present invention in an automobile.

[0049] The beneficial effects of the present invention are as follows: the fiber material and the thermoplastic material matrix in the composite foam material of the present invention have good interface compatibility and good interface micromorphology, which improves the compatibility between the fiber material and the thermoplastic material matrix, improves the mechanical properties of the composite foam material, and has the lightweight characteristics of low density and light weight.

[0050] The average cell radius of the composite foam material of the present invention is 15 μm to 30 μm, and the cell density is 2.0×10 6 Pieces / cm 3 ~1.6×10 7 Pieces / cm 3 , foaming density is 0.75g / cm 3 ~0.90g / cm 3 The porosity is 10% to 20%, the bending strength can reach 55 to 60 MPa, the tensile strength can reach 31 to 33 MPa, and the impact strength can reach 6.5 to 7.0 KJ / m 2 , combining light weight and excellent mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0051] Figure 1 The present invention is a flow chart for preparing the plant fiber reinforced composite material.

[0052] Figure 2It is a schematic diagram of the principle of the supercritical gas foaming method in the present invention.

[0053] Figure 3 This is a cross-sectional SEM image of the plant fiber reinforced composite material in Example 1 parallel to the melt flow direction.

[0054] Figure 4 This is a SEM image of the interface between bamboo fiber and polypropylene in the plant fiber reinforced composite material of Example 1.

[0055] Figure 5 This is a SEM image of the pore structure in the plant fiber reinforced composite material of Example 1. DETAILED DESCRIPTION

[0056] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. The reagents or instruments used that do not indicate the manufacturer are all conventional products that can be purchased commercially.

[0057] In some embodiments of the present invention, the present invention provides a composite foaming material, comprising the following raw materials in parts by weight: 45 to 85 parts of thermoplastic material, 10 to 40 parts of fiber material, 3 to 9 parts of coupling agent, 3 to 9 parts of nano inorganic particles, and 8 to 12 parts of toughening agent; the fiber material is alkali-treated plant fiber.

[0058] In some embodiments of the present invention, the composite foaming material is a supercritical gas foaming molding material.

[0059] In some embodiments of the present invention, the supercritical gas is selected from nitrogen, carbon dioxide or a combination thereof. In some embodiments of the present invention, the supercritical gas is nitrogen. In some embodiments of the present invention, the mass ratio of the amount of nitrogen used to the raw material for preparing the composite foaming material is (0.5-1):100.

[0060] In some embodiments of the present invention, the thermoplastic material is selected from at least one of polypropylene, polystyrene, polyethylene, polyvinyl chloride, polycarbonate, polyamide, and polyacrylate. In some embodiments of the present invention, the melt index of polypropylene measured at 230° C. and 2.16 kg load is 10 to 30 g / 10 min.

[0061] In some embodiments of the present invention, the plant fiber is selected from at least one of bamboo fiber, wood fiber, paper tendon, hemp fiber, and straw tendon. In some embodiments of the present invention, the fiber material is prepared by soaking the plant fiber in alkali solution at 50-70°C for 1-10 hours, then washing, drying, and crushing; In some embodiments of the present invention, the fiber material is prepared by soaking the plant fiber in alkali solution at 55-65°C for 3-6 hours, then washing, drying, and crushing.

[0062] In some embodiments of the present invention, the washing step is: washing the plant fiber with distilled water until the pH of the washed water is neutral.

[0063] In some embodiments of the present invention, the alkali solution is selected from sodium hydroxide solution, potassium hydroxide solution or a combination of the two.

[0064] In some embodiments of the present invention, the coupling agent is selected from polypropylene grafted with acrylic compounds; in some embodiments of the present invention, the coupling agent is selected from polypropylene grafted with maleic anhydride.

[0065] In some embodiments of the present invention, the nano inorganic particles are selected from nano montmorillonite.

[0066] In some embodiments of the present invention, the toughening agent is selected from SEBS.

[0067] In some embodiments of the present invention, the flexural strength of the composite foam material is not less than 55 MPa; in some embodiments of the present invention, the flexural strength of the composite foam material is 55-60 MPa.

[0068] In some embodiments of the present invention, the tensile strength of the composite foam material is not less than 30 MPa; in some embodiments of the present invention, the tensile strength of the composite foam material is 31-33 MPa.

[0069] In some embodiments of the present invention, the impact strength of the composite foam material is not less than 6KJ / m 2 In some embodiments of the present invention, the impact strength of the composite foam material is 6.5 to 7.0 KJ / m 2 .

[0070] In some embodiments of the present invention, the average pore size of the composite foam material is 15-30 μm.

[0071] In some embodiments of the present invention, the cell density of the composite foam material is 2×10 6 ~1.6×10 7 Pieces / cm 3 .

[0072] In some embodiments of the present invention, the density of the composite foam material is 0.75-0.9 g / cm 3 .

[0073] In some embodiments of the present invention, the porosity of the composite foam material is 10-20%.

[0074] In some embodiments of the present invention, the present invention further provides a method for preparing the composite foam material, comprising the following steps:

[0075] S1: mixing the prepared raw materials and then extruding and granulating them to obtain masterbatch;

[0076] S2: The masterbatch is injection molded, and supercritical gas foaming is used during the injection molding process to obtain a composite foam material.

[0077] In some embodiments of the present invention, reference Figure 1 The preparation flow chart in the figure, the preparation method of the composite foam material provided by the present invention comprises the following steps:

[0078] (1) first treating the plant fiber with alkali, then washing, drying and mechanically crushing to obtain a fiber material;

[0079] (2) mixing the fiber material, the thermoplastic material, the coupling agent, the nano inorganic particles and the toughening agent, and then extruding the mixture by a twin-screw extruder, and then hot-drying the mixture to obtain a blended masterbatch;

[0080] (3) injection molding the blended masterbatch at high temperature, and introducing supercritical gas during the injection molding process for micro-foaming to obtain the composite foam material.

[0081] In some embodiments of the present invention, step S1 is: mixing the prepared raw materials, extruding and granulating, and then drying at 100-150° C. for 4-10 hours to obtain a masterbatch.

[0082] In some embodiments of the present invention, the extrusion granulation step is: melt extrusion granulation is performed using an extruder, and the temperature of the extruder is set to: the temperature of zone 1 is 170-175°C, the temperature of zone 2 is 175-185°C, the temperature of zone 3 is 185-195°C, the temperature of zone 4 is 185-195°C, and the temperature of zone 5 is 175-185°C.

[0083] In some embodiments of the present invention, the injection molding step is: injection molding the masterbatch using an injection molding machine; the temperature of the injection molding machine is set to: the temperature of zone 1 is 180-185°C, the temperature of zone 2 is 185-195°C, the temperature of zone 3 is 185-195°C, and the temperature of zone 4 is 180-185°C.

[0084] In some embodiments of the present invention, during the injection molding step, the mold temperature is 40-50°C.

[0085] In some embodiments of the present invention, step S2 is to injection mold the masterbatch, use supercritical gas for foaming during the injection molding process, and then cool it to obtain a composite foam material.

[0086] In some embodiments of the present invention, in the cooling step, the temperature of the cooling liquid is 20-30°C.

[0087] In some embodiments of the present invention, the cooling time is 15 to 25 seconds.

[0088] In some embodiments of the present invention, the mass ratio of supercritical gas to the raw material for preparing the composite foaming material is (0.5-1):100. The principle of the present invention using supercritical gas for foaming is as follows Figure 2 As shown, specifically: during injection molding, nitrogen diffuses into the molten material to form a homogeneous system, then the bubbles nucleate and gradually grow, and finally during the injection molding and cooling process, the bubbles are shaped.

[0089] In some embodiments of the present invention, the pressure of the supercritical gas is 15-22 MPa.

[0090] In some embodiments of the present invention, the present invention further provides an automobile component, which is made of the above-mentioned composite foam material.

[0091] In some embodiments of the present invention, the automobile parts include automobile interior decoration parts, automobile exterior decoration parts, instrument panels, automobile compartment floors, automobile seat backs, and automobile armrests.

[0092] The implementation of the present invention is further described in detail below with reference to specific embodiments:

[0093] Example 1

[0094] This example provides a plant fiber reinforced composite material, the preparation steps of which are as follows:

[0095] (1) 4000g of bamboo fiber was repeatedly washed with distilled water to remove dust and other impurities on the surface. Subsequently, all the washed bamboo fibers were immersed in a 1.32mol / L NaOH solution and heated in a 60℃ water bath for 4 hours to dissolve impurities such as hemicellulose, gum, and wax in the fibers. The bamboo fibers were continuously washed with distilled water until the pH value of the washing water solution was neutral to obtain purified bamboo fibers, which were then dried for later use.

[0096] (2) 3000 g of dried bamboo fiber was crushed into granules with a length of 2 mm by a fiber crusher. 70 parts of polypropylene, 10 parts of bamboo fiber, 5 parts of maleic anhydride grafted polypropylene, 5 parts of nano-montmorillonite, and 10 parts of SEBS were weighed by mass and put into a high-speed mixer and stirred to mix well, cooled and discharged to prepare a premix.

[0097] (3) Add the premix to a twin-screw extruder, extrude and granulate, and then dry it: the drying temperature is 120°C, the drying time is 4 hours, and the premix masterbatch is obtained. The parameters of the twin-screw extruder are set as follows: the temperature of zone 1 is 170-175°C, the temperature of zone 2 is 175-185°C, the temperature of zone 3 is 185-195°C, the temperature of zone 4 is 185-195°C, and the temperature of zone 5 is 175-185°C.

[0098] (4) The premix masterbatch is placed in the barrel of a twin-screw injection molding machine, and supercritical gas (N2) is introduced during the injection molding process for foaming. After pressure relief and cooling, the plant fiber reinforced composite material in this example is obtained. The process parameters of the injection molding machine include: zone 1 temperature 180-185°C, zone 2 temperature 185-195°C, zone 3 temperature 185-195°C, zone 4 temperature 180-185°C; mold temperature 45°C, initial foaming gas dosage as a mass percentage of the total mass of the premix masterbatch is 0.5wt%, pressure is 18MPa, coolant temperature is 25°C, and cooling time is 20s.

[0099] Example 2

[0100] This example provides a plant fiber reinforced composite material. The preparation method of this example is different from that of Example 1 only in that in step (2) of this example, the mass fraction of polypropylene is 60 parts and the mass fraction of bamboo fiber is 20 parts.

[0101] Example 3

[0102] This example provides a plant fiber reinforced composite material. The preparation method of this example is different from that of Example 1 only in that in step (2) of this example, the mass fraction of polypropylene is 50 parts and the mass fraction of plant fiber is 30 parts.

[0103] Comparative Example 1

[0104] This example provides a polypropylene foam material, and the preparation method thereof is as follows:

[0105] 100 parts of polypropylene are weighed by mass and put into the barrel of a twin-screw injection molding machine for supercritical fluid (N2) foaming injection molding. After pressure relief and cooling, a polypropylene foam material is obtained. The process parameters of the injection molding machine include: zone 1 temperature 180-185°C, zone 2 temperature 185-195°C, zone 3 temperature 185-195°C, zone 4 temperature 180-185°C; mold temperature 45°C, initial foaming gas dosage accounts for 0.5wt% of the total mass of the premix masterbatch, pressure 18MPa, coolant temperature 25°C, cooling time 20s.

[0106] Comparative Example 2

[0107] This example provides a polypropylene material, and its preparation method is as follows: 100 parts of polypropylene are weighed by mass and put into the barrel of a twin-screw injection molding machine for direct injection molding, and after pressure relief and cooling, the polypropylene material is obtained. The process parameters of the injection molding machine include: the temperature of the first zone is 180-185°C, the temperature of the second zone is 185-195°C, the temperature of the third zone is 185-195°C, and the temperature of the fourth zone is 180-185°C; the mold temperature is 45°C, the coolant temperature is 25°C, and the cooling time is 20s.

[0108] Comparative Example 3

[0109] This example provides a plant fiber reinforced composite material, and its preparation method is different from that of Example 1 only in that: in step (2) of this example, the mass parts of polypropylene are 70 parts, the mass parts of bamboo fiber are 20 parts, and no high-efficiency toughening agent SEBS is contained.

[0110] Performance Test:

[0111] The mechanical properties and pore parameters of the materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were tested respectively, and the specific testing methods were as follows:

[0112] Mechanical property test: The materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were injected into test specimens using a plastic injection molding machine according to GB standard, and the test specimen sizes (length×width×thickness) were: tensile specimen (dumbbell type), 170.0mm×10.0mm×4.0mm; bending specimen, 80.0mm×10.0mm×4.0mm; notched impact specimen, 80.0mm×10.0mm×4.0mm, V-notch, notch depth is 1 / 5 of the thickness of the test specimen. Then the test specimen was placed in a standard environment with a temperature of (23±2)℃ and a humidity of (50±5)% for 16 hours and then tested. The test environment was (23±2)℃ and a humidity of (50±5)%, wherein the bending strength was tested according to the test method described in GB / T 9341-2008, and the bending speed was 1.25mm / min. The tensile strength was tested according to GB / T 1040.2-2022, with a tensile speed of 5 mm / min. The simply supported beam notched impact strength was tested according to GB / T1043.2-2018. At the same time, the heat aging performance test was carried out. The specific test steps are as follows: Cut the plastic sample to be tested into appropriate sizes and place it on the sample rack. Set the aging temperature and time parameters (100℃500 hours) and start the aging treatment. After the aging is completed, take out the sample and evaluate the corresponding color change grade according to GB / T 250-2008.

[0113] The mechanical properties and aging data measured according to the above test method are shown in Table 1 below.

[0114] Table 1 Mechanical properties and discoloration grade data after aging

[0115]

[0116] The cell parameter test method is: use a scanning electron microscope (SEM) to observe the cross section of the composite foam material at a high magnification, directly measure the radius of multiple cells, and take the average value to obtain the average radius of the cells; count the number of cells per unit area and calculate the cell density; determine the porosity by calculating the ratio of the area occupied by the pores to the total area. Accurately weigh the material mass, measure the material volume using the drainage method, and calculate the foam density. The cell parameters of the materials in Examples 1 to 3 and Comparative Examples 1 to 3 measured according to the above test method are shown in Table 2 below.

[0117] Table 2 Cell parameter test data

[0118]

[0119] It can be seen from Table 1 and Table 2 that compared with the polypropylene foam material in Comparative Example 1 and the pure polypropylene material in Comparative Example 2, the plant fiber reinforced composite material in the present invention has higher tensile strength (31-33 MPa), flexural strength (55-60 MPa) and impact strength (6.5-7.3 KJ / m 2 ). Moreover, the plant fiber reinforced composite materials in Examples 1 to 3 of the present invention have a color change level of 4 or above after heat aging at 100°C for 500h, no color difference change is obviously visible to the naked eye, and the decrease in mechanical strength is very small and can be ignored, and have good heat resistance stability. In addition, compared with the polypropylene material in Comparative Example 2, the plant fiber reinforced composite material in the present invention has low density, high mechanical properties, low cost, and is green and environmentally friendly.

[0120] The surface morphology of the plant fiber reinforced composite material in Example 1 parallel to the melt flow direction was tested by scanning electron microscopy. Figure 3 As shown, the surface morphology of the interface between bamboo fiber and polypropylene was tested. Figure 4 As shown, the SEM image of the pore structure of the plant fiber reinforced composite material in Test Example 1 is as follows Figure 5 As shown. Figure 3 to Figure 5It can be seen that in the plant fiber reinforced composite material of the present invention, the plant fiber and the polypropylene matrix produce excellent interface compatibility; the nano-montmorillonite particle additive effectively fills the micro gaps between the fiber and the polypropylene matrix, and effectively improves the interface bonding performance between the plant fiber and the polypropylene matrix; the addition of the high-efficiency toughening agent SEBS effectively improves the embrittlement and hardening problems caused by the addition of plant fibers to polypropylene, and improves the toughness of the composite material; the density of the material is effectively reduced through the supercritical gas microporous foaming process, and under the joint action of the plant fiber, nano-montmorillonite and SEBS, a large number of foaming micronuclei are induced to appear, the pore size is reduced, the pore density is increased, the bubbles are uniform and dense, and the mechanical properties are significantly improved.

[0121] In summary, compared with the fiber-reinforced composite materials in the prior art, the composite materials prepared by combining the supercritical gas foaming process with the alkali solution pretreatment process of plant fibers in the present invention have the following properties:

[0122] (1) The present invention can significantly improve the interfacial compatibility between plant fibers and polypropylene matrix by treating the surface of plant fibers with alkali solution, thereby solving the problems of poor compatibility and poor interfacial bonding between plant fibers and polymer matrix.

[0123] (2) The present invention adopts a supercritical gas microporous foaming method, which can improve the mechanical properties of the material while reducing the density of the material. Compared with the polypropylene material in Comparative Example 2, the bending strength of the material in the present invention is increased by 12.2% to 22.4%, the tensile strength is increased by 3% to 10%, the impact strength is increased by 62.5% to 82.5%, and the density is reduced by 9.8% to 17.6%, thereby realizing the preparation of low-density, high-strength lightweight plant fiber reinforced composite materials.

[0124] (3) The plant fiber in the present invention can induce the heterogeneous nucleation process in the polypropylene foaming process, thereby improving the foaming quality. Compared with the pure polypropylene foaming material in Comparative Example 1, the pore density of the composite material in the present invention is increased by 0.5 to 9.7 times, the pore size is reduced by 21.2% to 54.5%, and the problem of the difficulty in supercritical fluid foaming of existing polypropylene materials is solved.

[0125] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A composite foam material, characterized in that: The composite foaming material is prepared from the following raw materials in parts by weight: 45-85 parts of polypropylene, 10-40 parts of fiber material, 3-9 parts of maleic anhydride grafted polypropylene, 3-9 parts of nano-montmorillonite, and 8-12 parts of SEBS; the fiber material is alkali-treated plant fiber; the composite foaming material is a supercritical gas foaming molding material; the plant fiber is bamboo fiber; the mass ratio of the supercritical gas to the raw material for preparing the composite foaming material is (0.5-1):100; The pressure of the supercritical gas is 15-22 MPa.

2. The composite foam material according to claim 1, characterized in that: The preparation method of the fiber material comprises: soaking the plant fiber in alkali solution at 50-70°C for 1-10 hours, and then washing, drying and crushing the plant fiber to obtain the fiber material.

3. The composite foam material according to any one of claims 1 to 2, characterized in that: The composite foam material has at least one of the following characteristics: (a) the flexural strength of the composite foam material is not less than 55 MPa; (b) the tensile strength of the composite foam material is not less than 30 MPa; (c) The impact strength of the composite foam material is not less than 6KJ / m 2 ; (d) the average pore size of the composite foam material is 15-30 μm; (e) The cell density of the composite foam material is 2×10 6 ~1.6×10 7 Pieces / cm 3 ; (f) The density of the composite foam material is 0.75~0.9g / cm 3 ; (g) The porosity of the composite foam material is 10-20%.

4. The method for preparing a composite foam material according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1: mixing the prepared raw materials and then extruding and granulating them to obtain masterbatch; S2: injection molding the masterbatch, and using supercritical gas foaming during the injection molding process to obtain the composite foam material.

5. The method for preparing a composite foam material according to claim 4, characterized in that: The extrusion granulation step comprises: using an extruder for melt extrusion granulation, wherein the temperature of the extruder is set to: the temperature of zone 1 is 170-175°C, the temperature of zone 2 is 175-185°C, the temperature of zone 3 is 185-195°C, the temperature of zone 4 is 185-195°C, and the temperature of zone 5 is 175-185°C.

6. The method for preparing a composite foam material according to claim 4, characterized in that: The injection molding step comprises: using an injection molding machine to injection mold the masterbatch; the temperature of the injection molding machine is set to: the temperature of zone one is 180-185° C., the temperature of zone two is 185-195° C., the temperature of zone three is 185-195° C., and the temperature of zone four is 180-185° C.

7. An automobile component, characterized in that: The composite foam material comprises the composite foam material according to any one of claims 1 to 3.

8. Use of the composite foam material according to any one of claims 1 to 3 in automobiles.

Citation Information

Patent Citations

  • High barrier anti-aging water cup and preparation method thereof

    CN106397974A

  • Nanometer rice hull flour-reinforced polypropylene foam composite material and preparation method thereof

    CN107266785A

  • Microporous plant fiber composite material and preparation method thereof

    CN115536938A